Museum Matters : Making and Unmaking Mexico's National Collections - Rozental, Sandra; Deans-Smith, Susan, 1953-; Achim, Miruna (Book collections on Project MUSE., 2021)
"Museum Matters tells the story of Mexico's national collections through the trajectories of its objects. The essays in this book show the many ways in which things matter and affect how Mexico imagines its past, present, and future"--